2001
DOI: 10.1046/j.0022-0477.2001.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of mangrove tissues and implications for peat formation in Belizean island forests

Abstract: Summary 1Macrofaunal leaf consumption and degradation of leaves, woody twigs and roots were studied in mangrove island forests on a Belizean island. Factors influencing accumulation of organic matter deposited both above and below ground in this oligotrophic, autochothonous system were assessed. 2 Leaf degradation rates of Rhizophora mangle (red mangrove), Avicennia germinans (black mangrove) and Laguncularia racemosa (white mangrove) measured in mesh bags, were much faster in the lower than the upper intertid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
203
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(221 citation statements)
references
References 55 publications
(86 reference statements)
12
203
1
5
Order By: Relevance
“…The rest of the harvest consists of a mix of other shrimps, mud crabs, and other aquaculture products (Vu et al 2013;Jonell and Henriksson 2014). The GHG emissions from mangrove LULUC from shrimp farming were subsequently estimated to be 184 t CO 2 -eq t −1 live shrimp at farm gate using mass allocation and 282 t CO 2 -eq t −1 live shrimp using economic allocation (see ESM 2 for details on the calculations and Twilley et al 1992;Eong 1993;Matsui 1998;Kauffman et al 2011;Donato et al 2011;Ray et al 2011;Donato et al 2012 b Komiyama et al 1987;Twilley et al 1992;Matsui 1998;Kauffman et al 2011;Ray et al 2011;Donato et al 2012c Eong 1993Matsui 1998;Kauffman et al 2011;Ray et al 2011;Donato et al 2012;Lundstrum and Chen 2014 d Twilley et al 1992;Amarasinghe and Balasubramaniam 1992;Eong 1993;Day et al 1996;Middleton and McKee 2001;Jennerjahn and Ittekkot 2004;Guzman et al 2005;Ray et al 2011 e Twilley et al 1992;Eong 1993;Duarte and Cabrián 1996;Chmura et al 2003;Alongi 2008;Sanders et al 2010;Ray et al 2011;Mcleod et al 2011 Rewetted land, previously vegetated by mangrove, salinity >18 ppm kg CH 4 ha −1 year −1 0 R a n g e=0 -40 (uniform) IPCC 2014 assumptions behind them). Noteworthy is that these LULUC emissions only apply to Bmixed mangrove concurren...…”
Section: Greenhouse Gas Emissions From Shrimp Farming Luluc Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the harvest consists of a mix of other shrimps, mud crabs, and other aquaculture products (Vu et al 2013;Jonell and Henriksson 2014). The GHG emissions from mangrove LULUC from shrimp farming were subsequently estimated to be 184 t CO 2 -eq t −1 live shrimp at farm gate using mass allocation and 282 t CO 2 -eq t −1 live shrimp using economic allocation (see ESM 2 for details on the calculations and Twilley et al 1992;Eong 1993;Matsui 1998;Kauffman et al 2011;Donato et al 2011;Ray et al 2011;Donato et al 2012 b Komiyama et al 1987;Twilley et al 1992;Matsui 1998;Kauffman et al 2011;Ray et al 2011;Donato et al 2012c Eong 1993Matsui 1998;Kauffman et al 2011;Ray et al 2011;Donato et al 2012;Lundstrum and Chen 2014 d Twilley et al 1992;Amarasinghe and Balasubramaniam 1992;Eong 1993;Day et al 1996;Middleton and McKee 2001;Jennerjahn and Ittekkot 2004;Guzman et al 2005;Ray et al 2011 e Twilley et al 1992;Eong 1993;Duarte and Cabrián 1996;Chmura et al 2003;Alongi 2008;Sanders et al 2010;Ray et al 2011;Mcleod et al 2011 Rewetted land, previously vegetated by mangrove, salinity >18 ppm kg CH 4 ha −1 year −1 0 R a n g e=0 -40 (uniform) IPCC 2014 assumptions behind them). Noteworthy is that these LULUC emissions only apply to Bmixed mangrove concurren...…”
Section: Greenhouse Gas Emissions From Shrimp Farming Luluc Case Studymentioning
confidence: 99%
“…Sequestration rates have been estimated at between 228 and 766 t ha −1 year −1 Lundstrum and Chen 2014). Hypoxic conditions and the lack of other high-energy oxidants, in combination with a paucity of fungi, limit the opportunity for degradation, thereby providing good conditions for long-term storage of carbon (Middleton and McKee 2001). This, together with high biomass burial rates, the high potential age of mangrove trees, and a slow turnover rate, results in carbon storage rates relevant at global scales (Duarte et al 2005;FAO 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst it is clear that below-ground processes play an important role in coastal wetland stability (Nyman et al, 1995), the volume of sediment accreting on a wetland surface is the primary determinant of system response within the model. Sediment supply from in situ accumulation of organic sediments (Cahoon & Reed, 1995;Middleton & McKee, 2001;Rooth et al, 2003) or from external, inorganic inputs (French & Spencer, 1993;Christiansen et al, 2000) or a combination of the two, are used to characterise the impact of the environmental forcing factor within the DIVA model.…”
Section: Sediment Supplymentioning
confidence: 99%
“…Latitude, climate, species diversity and other biological factors also affect carbon fluxes in forests [3]. It has been reported that degradation of fresh organic matter is slower in anaerobic environments (such as mangroves), which additionally involves oxidizing agents such as nitrate and microorganisms like bacteria and fungi [6], which only operate when the tannin concentrations are low, because they inhibit growth [7][8]. The presence and abundance of macro invertebrates such as amphipods (crabs) and isopods (cochineal) also accelerates the breakdown of tissues by direct consumption of leaves [6].…”
Section: Introductionmentioning
confidence: 99%